Analysis of Determinants of Successful Digitalisation of Registration Services at Primary Healthcare Facilities in East Java on Patient Satisfaction Among JKN Participants: A Systematic Review - Ahmad Khusairi; Sedarmayanti Sedarmayanti; Ulul Albab; Nowshin Tabassum Taheri (International Journal of Social Science and Humanity, 2025)
This study analyses the challenges of digitalising registration services at Primary Healthcare Facilities (Fasilitas Kesehatan Tingkat Pertama, FKTP) in East Java, including limitations in human resources, technological infrastructure, and public digital literacy, all of which affect the satisfaction of National Health Insurance (Jaminan Kesehatan Nasional, JKN) patients. Utilising the Systematic Literature Review (SLR) methodology with the PRISMA approach, the study reviews literature from 2024–2025 sourced from databases such as Google Scholar, using keywords related to digitalisation, FKTP, and patient satisfaction. The analysis is based on the ADO (Antecedent, Decision, Outcome) framework. The findings identify three key factors: (1) Antecedents (human resource competence, infrastructure, digital literacy); (2) Decisions (human resource training, facility modernisation, public outreach); and (3) Outcomes (increased patient satisfaction through time efficiency and ease of access). The study emphasises the need to strengthen human resources, provide adequate infrastructure, and educate the public to ensure the sustainability of digital healthcare services at FKTPs in East Java.